Synthesis of New pyrazoline – phenoxazine Derivatives - Al-Araji, Suad; Ibraheem, Israa (Iraqi Journal of Science, 2025)
Phenoxazine prepared by the reaction of o-aminophenol with Zinc chloride in the presence of phosphoric acid. This work comprises the synthesis of new phenoxazine derivatives containing heterocyclic moieties. These heterocyclic compounds were synthesized in three groups. The first group is made up of 3-(oxoalk-en-1-yl)phenoxazine derivatives (3a-3g) obtained from the reaction of 10-acetyl- phenoxazine with different aromatic aldehyde in the presence of sodium hydroxide. The other two groups involve compounds produced from the reaction of (3a-3g) with hydrazine hydrate in acetic acid to get 10-(pyrazolin-3-yl)phenoxazine derivatives (4a-4g) and hydroxyl amine hydrochloride in the presence of ethanosodium hydroxide to afford 10-(1-phenyl pyrazolin-3-yl)phenoxazine derivatives (5a-5g). All these compounds of two groups above are substituted in position (5) in pyrazoline ring with different aryl groups according to aromatic aldehyde used in the preparation of the first group.